Endothelial procoagulant activity and release of endothelial cell-derived extracellular vesicles driven by antiphospholipid antibodies (2023)
ABSTRACT: Objective: Antiphospholipid syndrome (APS) is an autoimmune disease characterized by vascular thrombosis and pregnancy-related morbidity. APS is caused by antiphospholipid antibodies (aPL), but exact underlying pathogenic mechanisms remain unclear. This study explores the aPL-induced activation of endothelial cells, the subsequent release of extracellular vesicles (EVs), and the development of procoagulant effects. Methods: IgG fractions were purified from serum of 30 patients with different clinical manifestations of APS and 30 control volunteers. Human umbilical vein endothelial cells (HUVECs) were stimulated with IgG (250 µg/mL) in presence of MAPK pathway inhibitors. A plasma recalcification assay was used to determine their coagulation activity. EVs released by HUVECs were isolated by ultracentrifugation and analyzed using flow cytometry and nanotracking analysis (NTA). THP-1 cells (human monocyte cell line) were stimulated with the harvested EVs (1:50 cells:EVs ratio) and their procoagulant activity was assessed by a plasma recalcification assay. Results: Patients with pure obstetric APS (OAPS) exhibited decreased titers of aCL antibodies (mean: 10.15 IgG phospholipid units [GPL]) and increased responsiveness to treatment with low molecular weight heparin (LMWH) and aspirin (71%) compared to those having vascular and obstetric APS manifestations (VOAPS) (mean: 65.03 GPL, and 29%, respectively). Antibodies from patients with VOAPS and refractoriness to treatment increased the endothelial coagulation potential in a MEK1/2 and p38MAPK pathway-dependent manner (0.03 ± 0.013 vs 0.1 ± 0.03). This activation is accompanied by the release of endothelial-derived EVs which, according to our preliminary results, could increase the procoagulant activity of monocytes. Conclusions: Patients with pure OAPS are characterized by low aPL titers and high responsiveness to standard treatment. aPL from patients with obstetric manifestations accompanied by vascular thrombosis and refractoriness to treatment activates endothelial cells increasing their coagulation potential. EVs released in this context could increase the procoagulant activity of monocytes amplifying the hypercoagulable state observed in APS.